(untitled) (Perner’s Contacts, 2011)
The article deals with the development of UMTS networks, evaluating the properties of public mobile networks, 3G (T-Mobile, Telefónica and Vodafone) on the basis of experimental measurements and the possibility of use in traffic control and information systems.